1999
DOI: 10.1038/15260
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for T-cell apoptosis in the induction of peripheral transplantation tolerance

Abstract: The mechanisms of allograft tolerance have been classified as deletion, anergy, ignorance and suppression/regulation. Deletion has been implicated in central tolerance, whereas peripheral tolerance has generally been ascribed to clonal anergy and/or active immunoregulatory states. Here, we used two distinct systems to assess the requirement for T-cell deletion in peripheral tolerance induction. In mice transgenic for Bcl-xL, T cells were resistant to passive cell death through cytokine withdrawal, whereas T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
427
4
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 574 publications
(453 citation statements)
references
References 24 publications
20
427
4
2
Order By: Relevance
“…Recent studies show that IFN-c and IL-2 promote allograft acceptance in vivo (Konieczny et al 1998;Wells et al 1999). Accordingly, our data showed higher levels of IL-2 and IFN-c in the group without GVHD compared to the GVHD group.…”
Section: Cytokine Release and Significance Of Cytokines In Clinical Tsupporting
confidence: 68%
“…Recent studies show that IFN-c and IL-2 promote allograft acceptance in vivo (Konieczny et al 1998;Wells et al 1999). Accordingly, our data showed higher levels of IL-2 and IFN-c in the group without GVHD compared to the GVHD group.…”
Section: Cytokine Release and Significance Of Cytokines In Clinical Tsupporting
confidence: 68%
“…These drugs, however, prevent up-regulation of CD95L after T cell activation and therefore inhibit AICD. In contrast RAP does not block AICD [26].…”
Section: Introductionmentioning
confidence: 74%
“…The importance of apoptosis induction for peripheral transplantation tolerance has been demonstrated in recent reports [26,49]. Wells et al showed that mice transgenic for bcl-x L expression in T cells or IL-2 deficient mice are resistant to the induction of transplantation tolerance due to defective passive or active T cell apoptosis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrating the importance of alloreactive T-cell deletion during tolerance induction have promoted use of peritransplant T-cell-depleting therapies in clinical trials [3][4][5][6] . But potentially complicating wide-scale, nonspecific T-cell depletion is the finding that extensive T-cell proliferation can occur under conditions of lymphopenia.…”
Section: Introductionmentioning
confidence: 99%